Management of speech, language and communication difficulties in Huntington''s disease. (February 2012) - Hamilton, Alison; Ferm, Ulrika; Heemskerk, Anne-Wil; Twiston-Davies, Rita; Matheson, Kirsty Y; Simpson, Shiela A; Rae, Daniela
SUMMARY Speech and language therapists play an important role in the management of communication difficulties in Huntington''s disease (HD). As the disease progresses the effectiveness of communication becomes increasingly compromised by a combination of changes in motor function, diminishing cognitive linguistic abilities and neuropsychiatric changes, such as depression and apathy. The complexities and challenges presented by communication breakdown in HD require comprehensive assessment and interventions that are responsive to the changing motor, cognitive and emotional needs of the individual. The European Huntington''s Disease Network Standards of Care Speech and Language Therapy Working Group has brought together expert speech and language therapists from across Europe to produce guidelines to improve the management of communication disorders for individuals with HD. The guidelines were developed with the aim of promoting timely and appropriate assessment and focused management throughout all stages of the disease. Literature was thoroughly searched and evaluated in an attempt to ensure that the guidelines are based on available evidence. However as there is a paucity of good-quality, high-level evidence the guidance is based predominantly on expert opinion and consensus. The provision of care varies widely between countries in Europe and the implementation of these guidelines aims to help improve the quality of care delivered to individuals with HD.